The bZIP transcription factor VdAtf1 regulates virulence by mediating nitrogen metabolism in Verticillium dahliae. Issue 5 (16th March 2020) - Tang, Chen; Li, Tianyu; Klosterman, Steven J.; Tian, Chengming; Wang, Yonglin
Summary: The fungus Verticillium dahliae causes vascular wilt disease on hundreds of plant species. Homologs of the bZIP transcription factor Atf1 are required for virulence in most pathogenic fungi, but the molecular basis for their involvement is largely unknown. We performed targeted gene deletion, expression analysis, biochemistry and pathogenicity assays to demonstrate that VdAtf1 governs pathogenesis via the regulation of nitrosative resistance and nitrogen metabolism in V. dahliae . VdAtf1 controls pathogenesis via the regulation of nitric oxide (NO) resistance and inorganic nitrogen metabolism rather than oxidative resistance and is important for penetration peg formation in V. dahliae . VdAtf1 affects ammonium and nitrate assimilation in response to various nitrogen sources. VdAtf1 may be involved in regulating the expression of VdNut1 . VdAtf1 responds to NO stress by strengthening the fungal cell wall, and by causing over‐accumulation of methylglyoxal and glycerol, which in turn impacts NO detoxification. We also verified that the VdAtf1 ortholog in Fusarium graminearum mediates nitrogen metabolism, suggesting conservation of this function in related plant pathogenic fungi. Our findings revealed new functions of VdAtf1 in pathogenesis, response to nitrosative stress and nitrogen metabolism in V. dahliae . The results provide novel insights into the regulatory mechanisms of the transcription factor VdAtf1 in virulence.